Comprehension Of The "Gap" Phenomenon In Outsourced Development Projects, Including The Dimensions Of The Gap: A Research Investigation - Xiu, Liu; Ali, Dhakir Abbas (Journal of Neonatal Surgery, 2025)
The "gap" effect in outsourced IS development projects, which lowers stakeholder happiness, outcomes quality, and project satisfaction overall. This exploratory study seeks to fill light on the numerous facets of the gap in outsourced IS development and its implications for project management by examining its extensive nature. Although outsourcing is often used by organizations to save money and get access to specialized skills, it may sometimes cause issues that reduce project performance. This study identifies and analyzes common gaps in outsourced IS projects, including communication hurdles, cultural issues, and expectations misalignment. In order to capture the complexities and variations of the gap phenomenon across varied project contexts, the research utilizes case studies, interviews, and industry reports. One area that has been looked at is the communication gap, which encompasses issues with the flow of information and the customer's and outsourced vendor's awareness of each other. When individuals on a project have different expectations, priorities, and ways of approaching issues, researchers often point to cultural differences as a possible explanation. Disparities between actual and anticipated deliveries must be investigated in order to learn more about the expectations gap's effects on project outcomes and stakeholder happiness. By highlighting these features, the research hopes to provide a deeper understanding of the gap phenomenon and practical remedies. A thorough approach that includes better communication strategies, more cultural awareness, and clear expectations from the beginning may help bridge the gap